Pursuing Empire: Brazilians, the Dutch and the Portuguese in Brazil and the South Atlantic, c.1620-1660
1 online resource
Keywords: Peoples living on the shores of the South Atlantic during the first sixty years of the seventeenth century were confronted with challenges imposed by colonial occupation, disputes between empires and continuous warfare. While the future of the Dutch and Portuguese empires was being decided with unparalleled violence, common people faced daily challenges to survive institutional and political interests beyond their control. This book takes the perspective of individuals, families and groups of interest in their daily strive to survive a European pursuit of empire. Contributors are: Cátia Antunes, Francisco Bethencourt, Filipa Ribeiro da Silva, José Manuel Santos-Pérez, Marco António Nunes da Silva, Bruno Romero Ferreira Miranda, Anne B. McGinness, Thiago Nascimento Krause, Christopher Ebert, and Amélia Polónia.